Análise de esforços eletromagnéticos nos enrolamentos de transformadores ocasionados por correntes de curto-circuito e corrente de inrush - LIMA, Diorge de Souza (2018)
Power transformers are very important equipment for the national electric system, being responsible for viability in the context of transmission and enable the connection of centers generators, industries and end consumers. In this perspective, due to its importance, the design of these devices must be performed predicting more severe situations that may be submitted. Every moment these devices are exposed to currents of transient states that can cause defects or malfunctions. Therefore, the practice shows numerous failures in these devices, among the most frequent causes stand out electromechanical efforts in windings caused by transient states. In this perspective, this study aims to analyze computational method through the behavior of transformers when subjected to the current of short-circuit and inrush. For this analysis the finite element method (FEM) modeling of an experimental three-phase transformer of 15 kVA and a single-phase of 50 MVA transformer used by a power generation company in the Northern region of Brazil. Thus, the conditions of asymmetric faults are used to estimate the density of magnetic stray field of the transformer and find the values of forces in radial and axial components. The method used consists of the discretization of a continuous medium in small elements maintaining its original character, being a form of numerical solution of a system of partial differential equations. For it will be presented in detail all the steps to obtaining the results from the pre-processing, processing to post-processing. Finally, results of computational analyzes will be presented and compared with results from references cited in this work. Therefore, all computational results are compared to numerical results obtained from the formulations provided by this work.